Dead Weight Tester Untuk Penggunaan Internal PLTG Tanjung Uncang - Zulferi Syahputra; Eben Ezer Situmorang; Renaldi Pamungkas; Qoriatul Fitriyah; Muhammad Prihadi Eko Wahyudi (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2023)
In the industrial world, many instruments are installed as tools and devices used for measurement and control in a larger and more complex system, especially at the Tanjung Uncang Gas Power Plant in Batam. To ensure the accuracy of measuring instruments and instrument devices are functioning properly, periodic maintenance or recalibration is required. In general, every calibration of the measuring instrument is carried out by an external party to the company, and it requires additional operational costs for the company. From the results of observations in the field, the author tries to make one simple calibration tool, namely the pressure gauge dead weight tester which is only used for internal company use. This tool can work with a pressure range of 0-100 psi using a weight of 1 kg to 17 kg. which has been tested to calibrate the pressure gauge type C bourdon 2.5 bar and 7 bar with a small error between 0% - 3% and by analysis using linear and polynomial regression methods, the data generated in testing this tool is close to a value of 1 (R Square) which can be used as a reference for the pressure gauge calibration process with a range of 0 - 7 bar.